Efektivitas Pestisida Nabati Terhadap Pengendalian Hama Kutu Kebul (Bemisia tabaci Genn.) pada Tanaman Tomat (Lycopersicum esculentum Mill.) - NUR FITRIYAH; Widyana Rahmatika; Kintan Adinda Dheandra (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2023)
his observation aims to determine the level of effectiveness of the organic pesticide garlic and tobacco against the control of whitefly pests (Bemisia tabaci) and production of tomato (Lycopersicum esculentum) which was conducted from 3rd October until 20th December 2022 at UNISKA Kediri field laboratory. The study was conducted at the UNISKA Kediri field laboratory with a known pH of 5 with sandy loam soil type was conducted from October 03, 2022 to December 20, 2022. The research method used a non-factorial Randomized Group Design. The factors is type of vegetable pesticides (garlic and tobacco) with each consisting of four concentration levels of 0%, 20%, 40% and 60% so that there are 8 kinds of combination, carried out as many as 4 replicates and 3 samples of tomato plants were taken and used 96 sample of plants and about 1000 whitefly. After data was obtained, a varians analysis was carried out if there was continued with BNT 5% test. From the observation, it is known that the types of pesticides have a significant effect on the mortality rate of whitefly pests, while the concentration have a very significant effect on the mortality rate of whitefly with abest dose is 60% , but there is no interaction between the two single factors. In addition, the application of the organic pesticides does not have an effect on the growth and production of tomato, this is because organic pesticide isn’t type of nutrients that can help the growth and production on tomatoes